Madagascar : Development Policy Review, Sustaining Growth for Enhanced Poverty Reduction, Volume 1, Main Report - World Bank (Washington, DC, 2012)
The country's approach to poverty reduction is outlined in the 2003 Poverty Reduction Strategy Paper, and draws on a development approach in which growth and poverty reduction are mutually reinforcing. Three areas of focus are identified in the PRSP: (1) restoration of law and improvements in governance; (2) promotion of broad-based growth; and (3) promotion of systems for establishing human and material security. The DPR presents Madagascar's development policy agenda in an integrated framework within which issues of policy consistency, priorities, and sequencing could be addressed. This DPR focuses on growth and growth strategy. It highlights the main structural and institutional impediments to achieving sustained growth and the factors constraining the ability of the poor to participate in economic growth. Emphasis is put on issues and sectors that contribute directly to growth: private sector development issues, including the availability of credit; elements of competitiveness such as infrastructure and education; and issues in sectors considered sources of growth. While the impact of government policy on poverty i s most directly felt through public expenditure and service delivery, these are dealt with in great detail in the accompanying PER, and will only be touched upon here in the context of government's growth strategy. Finally, the DPR identifies the main sources of vulnerability of the country.